Pathways to Education: An Integrated Approach to Helping At-Risk High School Students - Oreopoulos, Philip; Brown, Robert S.; Lavecchia, Adam M. (Journal of Political Economy, 2017)
Pathways to Education is a comprehensive support program developed to improve academic outcomes of high school students from very poor social-economic backgrounds. The program includes proactive mentoring, daily tutoring, and group activities, combined with intermediate and long-term incentives to reinforce a minimum degree of mandatory participation; it began in 2001 for entering grade 9 students living in Regent Park, the largest public housing project in Toronto. It expanded in 2007 to include two additional Toronto projects. Comparing students from other housing projects before and after the introduction of the program, high school graduation and postsecondary enrollment rates rose dramatically for Pathways-eligible students, in some cases by more than 50 percent.